Beliefs and practices of cultural care of women with severe maternal morbidity (2018)
The present study aimed to describe the beliefs and practices of cultural care in women who had major causes of severe maternal morbidity, not in the prenatal control and attended at an institution of III level of health care in the city of Medellín. It was a research of a qualitative, ethnographic type, a method used was the ethno-infertility proposed by Leininger, the sample composed of 17 women with severe maternal morbidity, not in control of prenatal, who were interviewed several times until data saturation was achieved; Then, they were collected and analyzed through the ethnographic analysis proposed by Spradley. Results: 5 general themes and 2 taxonomies were found. The study concluded that women with severe maternal morbidity, unresponsive to prenatal care, have their own modes of care for themselves and the unborn child when they are ill, because access to maternal health services is deficient. Similarly, the nursing care offered to these women should be based on the knowledge of cross-cultural nursing proposed by Leininger. Keywords: Nursing, ethno-nursing, care, cultural care, severe maternal morbidity